STUDY OF MOLECULAR MECHANISMS INVOLVED IN CARDIOPROTECTIVE ACTION OF DEXRAZOXANE AGAINST ANTHRACYCLINE CARDIOTOXICITY IN RABBITS. (21st November 2014) - Jirkovsky, E; Lencova, O; Jirkovska, A; Potuckova, E; Hroch, M; Adamcova, M; Simunek, T; Gersl, V; Sterba, M
Abstract : So far dexrazoxane (DEX) is the only drug approved for prevention of chronic anthracycline (ANT) cardiotoxicity. However, molecular mechanisms responsible for its cardioprotective effects remain unclear. This report addresses traditional as well as alternative mechanisms of its cardioprotective action against chronic ANT cardiotoxicity. Daunorubicin (DAU, 3 mg/kg/week for 10 weeks) was used to induced cardiotoxicity in rabbits and DEX (60 mg/kg) was administered prior each DAU dose. LV myocardium was analyzed for oxidative stress, mitochondrial damage, changes in mtDNA and mtDNA/nDNA ratio, and perturbations in mitochondrial proteins expression. DEX ability to interact with iron was addressed in H9c2 cardiomyoblasts. In addition, topoisomerase-2β (TOP2b) expression was studied after DEX exposure in vitro and in vivo. DEX completely prevented DAU-induced heart damage as well as mitochondrial damage. This protection was not directly based on protection from oxidative damage of myocardium or common deletion in mtDNA. Instead, DEX was able to prevent DAU-induced significant decrease in expression of mitochondrial biogenesis regulators (e.g. TFAM) and OXPHOS subunits encoded by both nDNA and mtDNA. Noteworthy, in vitro experiments showed inability of DEX to mobilize iron from cells. Finally, DEX exposure decreased TOP2b protein levels which can correspond with recent data showing that ANT cardiotoxicity may beTOP2b-mediated. The present data suggest that DEX cardioprotective effects need not be based on iron chelation and prevention of oxidative stress or mtDNA deletions. Instead, DEX-induced depletion of TOP2b may be important for cardioprotection and merit further study. Supported by GACR 13–15008S and PRVOUK P37/05.